Computational collective intelligence. technologies and applications : 6th International Conference, ICCCI 2014, Seoul, Korea, September 24-26, 2014. Proceedings - Jung, Jason J.; Nguyen, Ngoc-Thanh; Hwang, Dosam (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed proceedings of the 6th International Conference on Collective Intelligence, ICCCI 2014, held in Seoul, Korea, in September 2014. The 70 full papers presented were carefully reviewed and selected from 205 submissions. They address topics such as knowledge integration, data mining for collective processing, fuzzy, modal and collective systems, nature inspired systems, language processing systems, social networks and semantic web, agent and multi-agent systems, classification and clustering methods, multi-dimensional data processing, Web systems, intelligent decision making, methods for scheduling, image and video processing, collective intelligence in web systems, computational swarm intelligence, cooperation and collective knowledge.